A new species of Amyris (Rutaceae, Toddalioideae, Amyridinae) from Mexico - Hernández-Barón, Lizetth Jimena; Espejo-Serna, Adolfo; Pérez-García, Eduardo A.; Cerros-Tlatilpa, Rosa; López-Ferrari, Ana Rosa (Phytotaxa, 2016)
Amyris jorgemeavei from the state of Oaxaca, Mexico, is described and illustrated. The new taxon is compared with A. carterae and A. madrensis, species with similar morphological characteristics. It is however easily differentiated from these two by having glabrous leaves and floral parts, a lobed nectar disc, and it is known only from southwestern Mexico. A comparative table and a distribution map of the three species are included.